Panorama geral da certificação de sementes no Estado de Goiás - Silva, Junior Moisés da (2011)
This study aimed to identify the structure surrounding the certification of seeds in the State of Goiás, tacking into account the approved area, production and commerce of seeds of the most important species for the State during the agricultural years of 2008/09 and 2009/10. For both data collections were made at the Ministry of Agriculture and Supplying as the certification, the credential and particular certifiers laboratories and official laboratories, certifiers own production, traders, repackaged and samplers. On the other hand certifiers were also questioned about quality of its certifications, with questions about staff, its own laboratories, certify the cost to the different species/category, activity in Goiás and other states and pertinent subjects as impediments and perspectives to the certification in Goiás and expectations to the trade of seeds. With the gotten information it was concluded that the production chain is adequately equipped, structurally as technical, needing however of one better organization between its some links. It was also verified in Goiás toward all the categories the biggest production of seeds is come back toward maize and soy, therefore in such a way the register of areas and the commercialization of these seeds also follows the same trend.